2023
DOI: 10.1111/cch.13113
|View full text |Cite
|
Sign up to set email alerts
|

The association between home learning during COVID‐19 lockdowns and subsequent school attendance among children with neurodevelopmental conditions

Abstract: Background Children with neurodevelopmental conditions have high levels of school absence. During the COVID‐19 pandemic, schools closed for many students. The relationship between home learning during school closures and subsequent school attendance requires attention to better understand the impact of pandemic education policy decisions on this population. This study aims to investigate the association between home learning, hybrid learning and school learning during school closures (in January–March 2021) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…chronic, persistent, continuous, or frequent). The most common definition was 10% of school time, which was used in seven studies ( K. P. Anderson, 2021 ; Hatton, 2018 ; Jarbou et al, 2022 ; John et al, 2022 ; Kouroupa et al, 2023 ; Mattson et al, 2022 ; Totsika et al, 2020 ). Other definitions included 30 days/year, 4 weeks/year, 3 days/20 days, more than 1 week, or 11 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…chronic, persistent, continuous, or frequent). The most common definition was 10% of school time, which was used in seven studies ( K. P. Anderson, 2021 ; Hatton, 2018 ; Jarbou et al, 2022 ; John et al, 2022 ; Kouroupa et al, 2023 ; Mattson et al, 2022 ; Totsika et al, 2020 ). Other definitions included 30 days/year, 4 weeks/year, 3 days/20 days, more than 1 week, or 11 days.…”
Section: Resultsmentioning
confidence: 99%
“…The parents stressed the importance of a partnership between home and school, to address the problem early, and to stop using the term school refusal. One study found that a reason for selecting elective home education was to avoid exclusion from school ( Paulauskaite et al, 2022 ), while one study ( Kouroupa et al, 2023 ) reported that school attendance problems increased during school closure in a group of children with autism and/or intellectual disability.…”
Section: Resultsmentioning
confidence: 99%